7 - Symbolic violence, academic capital and reflexivity: A case-study of post-apartheid curriculum change for teacher education using Bourdieu - Dirk, Wayne Peter (African Sociological Review, 2022)
This paper provides an account of a failed attempt to transform the teacher education curriculum in the Faculty of Education at a historically white university in South Africa. Based on a larger study, the paper argues that academics in the Faculty were strongly allied to the apartheid- tainted education philosophy of Fundamental Pedagogics (FP) that caused them to resist curriculum transformation. Using their dominant positions, the senior academics undermined the transformation process by deceiving the administrative structures of the university. Using Bourdieu’s signature concepts of field, habitus, capital and hysteresis (a condition in which the habitus is no longer in synch with a field that is undergoing fundamental change), this paper argues that the practices of the senior academics were acts of symbolic violence because they arbitrarily chose to continue the established culture of FP that was targeted for transformation by the university. The institutional power of the senior Professors that enabled their practice of symbolic violence is explained with the concept of academic capital. Bourdieu’s theory of reflexivity is discussed as a practical intervention that has the potential to assist academics and university managers to limit the effects of symbolic violence in curriculum production. In closing, the paper briefly touches on the recent student protests at South African universities and argues for the extension of Bourdieu’s conceptualisation of symbolic domination to include the relationship between symbolic and physical violence, which is a neglected area of higher education studies, particularly in societies with a history of colonialism and racialised social inequality.